Mechanisms of Human Immunodeficiency Virus-Associated Lymphocyte Regulated Cell Death - Paim, Ana C. (AIDS Res Hum Retroviruses, 2020)
Human immunodeficiency virus-1 (HIV-1) causes CD4 T cell depletion through a number of mechanisms, including programmed cell death pathways (both apoptotic and nonapoptotic). In the setting of HIV-1 infection, the enhanced lymphocyte cell death occurs as a consequence of complex interactions between the host immune system and viral factors, which are reviewed herein. On the other hand, the main challenge to HIV-1 eradication is the development of latent infection in a subset of long lived cells, including CD4(+) T cells and macrophages, which resist HIV-induced cell death. Understanding the potential mechanisms of how HIV-1 induces lymphocyte cell death is critical to the “kick and kill” cure strategy, which relies on the effective killing of reactivated, HIV-1-infected cells.